Haematology and Serum Biomakers of Broiler Birds Fed Graded Levels of Clove (Sygzium aromaticum (L.) Buds Meal in Semi Arid Nigeria - , H. B. Usman, K. M. Aljameel, M. M. Mika’ilu, S. A. Maigandi, A. Z. Sanusi, S. Ibrahim (Archives of Current Research International, 2021)
The study investigated the effect of graded levels of cloves bud powder on broiler birds. The study was conducted using a total of 288 broiler birds in a Completely Randomized Design Four treatments; four experimental diets where formulated and designated as T1 (control), T2 (0.5kg/100kg), T3 (1Kg/100kg) and T4 (1.5kg/100Kg). At the end of the feeding trial (eighth week), fifteen birds (5 per replicate) from each treatment group were randomly selected for blood collection. About 2ml of blood were collected per bird. Birds in treatment 4 (1.5kg/100kg) had the highest (P<0.05) concentration of haemoglobin and PCV compared to treatment 1 (control) and 3 (1kg/100kg). Significant difference (P<0.05) was observed in albumin, globulin, total protein, HDL, cholesterol, urea, AST and ALT. The result shows that birds fed 1.5/100kg clove buds meal have higher albumin, globulin and total protein. The study conclude that inclusion of clove buds meal up to 1.5/100kg in diet of broiler birds without adverse effect as in indicated by haematological and serum biochemical of the birds in this study.